Subsídios para implantação de sistema de gestão ambiental segundo a NBR ISO 14001:2004. Um estudo de caso - Barreto, Paulo Leitao (2011)
This paper presents the parameters that should guide an environmental management system for a car dealership in Santa Maria, RS. taking as a basis the technical recommendations contained in ISO 14001. To this end, carried a diagnosis in the workshops of the company, at which time it was possible to observe, record, analyze and propose the guidelines compared to the management system of the undertaking, taking into account their specificities. The work has taken as a strategy to identify the waste management practices recommended in the technical literature, proper waste management in workshops, and the diagnosis of environmental auditing, verifying the conditions of waste management, wastewater and other related aspects potentially polluting activities; the diagnosis of environmental auditing, verifying the conditions of waste management, wastewater and other aspects related to the potentially polluting activities, and a comparative analysis of the environmental management practices outlined in ISO 14001, and the critical aspects of risk of pollution found in the workshops of the company studied. The research presented is applied to the type of qualitative approach, and the introduction is presented in five chapters, which include the review of theoretical concepts on the subject, the company characteristics and environmental conditions of their interaction, and an analysis on the issues essential to the organization's environmental management. From the study it can be inferred that the company has, in many respects, good management of the processes that can impact the environment, however, need to formalize an environmental management system in order to excellence necessary procedures for sustainability legal compliance and competitiveness.